Prevention of Motor Vehicle Theft by the Samapta Patrol (Study at the Demak Resort Police) - Lesha Syabrina (Universitas Negeri Semarang, 2023)
This study is to describe the samapta patrol units and efforts increased by the Demak Police samapta unit. This type of research uses a field of research and a qualitative approach. Data sources include primary data and secondary data with data collection techniques used are interviews, observations, and document studies Data analysis techniques used include data reduction, data presentation and conclusion drawing. Knife analysis in conducting discussions includes POAC theory and management theory. The results of the study found that curanmor crimes had fluctuated over the past three years, patrol activities carried out by the Samapta Unit of the Demak Police were carried out according to the SOP, divided into four stages, namely preparation stage, organization stage, implementation stage and evaluation/ termination stage. Some actors are inadequate and external facilities and infrastructure are the jurisdiction of the Demak Police which is quite wide and the intentions of criminals are difficult to predict. Based on the results of the study, the author suggests that in the creation of patrol routes always pay attention to the development of the last Kamtibmas situation in Kabupaten Demak. Often establish cooperation with the community, such as Hansip post, Kamra post, Security Guard post, and Kamling post selectively to facilitate monitoring locations prone to theft of motor vehicles and patrols through residential areas of the community.